Tensile Testing of Steel for the Reinforcement (Proceedings of Faculty of Civil Engineering, 2023)
The paper describes in detail the tensile testing of steel for the reinforcement according to the HRN EN ISO 15630‐1:2010 norm. The aforementioned norm refers to the HRN EN ISO 6892‐1:2016 norm, which, due to the dependence of the mechanical properties of steel on the test speed, recommends method A that uses strain control. Tensile testing of steel for the reinforcement B500B was performed on three samples using method A1 of the same norm. The aim of the paper is to bring readers closer to the issue of ensuring the conditions for tensile testing of steel for the reinforcement with strain control and to provide guidelines for the application of the norm. The results of tensile test on steel for the reinforcement show that the Zwick Z 600E universal testing machine can provide strict tolerance limits on strain control rates.
Keywords: steel for the reinforcement; tension; norm; laboratory test